Vpliv indeksa dinamične moči na odrivne in sprinterske sposobnosti športnikov - Spudić, Darjan (Šport (Ljubljana), 2022)
The dynamic strength index (DSI), also known as dynamic strength deficit or explosive strength deficit, is a variable that represents the relationship between an athlete’s ballistic peak force and maximum voluntary isometric contraction test force (MVIC). The purpose of this study was to evaluate the correlations between MVIC and DSI variables on jumping and sprinting performances. The study encompassed the testing of Physical Education students (n = 43). They performed ankle extensions, half-squats and deadlift MVIC tests, vertical jump tests, and 30-m sprint tests. DSIs were calculated between the combinations of the force obtained in the ballistic tests and the force obtained in the MVIC tests. We found no linear correlations between DSI and jump or sprint performances. On the contrary, linear correlations were found between jump and sprint performances and MVIC test results. Based on the results of our study, we can conclude that DSI cannot be used as a predictive metric for jump and sprint performances. We found higher predictive values for jump and sprint performance among MVIC tests. The isometric olympic bar pull test independently explained 21 to 50 % of the variability in jump performances and the isometric half-squat tests independently explained 16 to 40 % of the variability in sprint performances. Given the low predictive values of the broad range of calculated DSI variables for jumping and sprinting performances (which are the main components of sport successfulness), DSI-based training is questionable and should be further explored.
Keywords: balistični trening; meritve; moč; odriv; sprinti; šport; športniki; testiranje; trening moči